2018
DOI: 10.1002/jcp.27206
|View full text |Cite
|
Sign up to set email alerts
|

miR‐200a‐5p augments cardiomyocyte hypertrophy induced by glucose metabolism disorder via the regulation of selenoproteins

Abstract: Selenium and selenoproteins are identified as potential determinants in pathological cellular hypertrophy. Cardiomyocytes hypertrophy is a compensatory form of heart disease characterized by increased size of cardiomyocytes. However, the link between cardiac hypertrophy and Se-specific microRNA (miRNA) remains to be characterized. In the current study, we established a miR-200a-5p mimic and an inhibitor cardiomyocytes model. Cardiomyocytes hypertrophy was induced in the miR-200a-5p mimic group. Hence, we detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…Further, circulating miR-200c correlates with cardiac hypertrophy and diastolic dysfunction as assessed by E/e ′ and miR-200a with cardiac hypertrophy and arterial stiffness. In light of the findings of the present work and of the previously described negative effects of miR-200c and miR-200a on endothelial [24,25,29,63] and vascular smooth muscle cells [31] and cardiac [45][46][47] function, the upregulation of these miRNAs could play a role in the inflammation and oxidative stress upregulation, increasing the risk of adverse CV events in psoriatic patients.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Further, circulating miR-200c correlates with cardiac hypertrophy and diastolic dysfunction as assessed by E/e ′ and miR-200a with cardiac hypertrophy and arterial stiffness. In light of the findings of the present work and of the previously described negative effects of miR-200c and miR-200a on endothelial [24,25,29,63] and vascular smooth muscle cells [31] and cardiac [45][46][47] function, the upregulation of these miRNAs could play a role in the inflammation and oxidative stress upregulation, increasing the risk of adverse CV events in psoriatic patients.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, miR-200c and miR-200a have been recently associated with cardiac hypertrophy in animal models [45][46][47]; further, both miR-200c and miR-200a target SIRT1 [25,53], and in addition, we demonstrated that miR-200c targets eNOS, contributing to endothelial dysfunction establishment increasing ROS and decreasing NO, that is a potent vasodilator necessary for endothelial function preservation…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 52%
See 1 more Smart Citation
“…59 In particular, the expression of miR-200a-5p is significantly increased in several cancer types 44,45,47 and heart diseases. 63,64 In our study, miR-200a-5p has been shown to regulate TAP1 expression in HEK293T and melanoma cells. MiR-200a-5p was initially found by in silico prediction to bind Figure 8.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, it is extremely important to highlight the role of micro RNA (miR). miR is a short and noncoding RNA that interacts with the 3-untranslated region (UTR) of mRNAs blocking gene expression, degrading mRNAs and regulating protein expression ( Winter et al, 2009 ; Krol et al, 2010 ; Qi et al, 2019 ; Yang et al, 2019 ).…”
Section: Oxidative Stress and Epigenetics Factors As Camkii Regulatormentioning
confidence: 99%